2020
DOI: 10.1186/s13643-020-01449-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between pregnancy intention and late initiation of antenatal care among pregnant women in Ethiopia: a systematic review and meta-analysis

Abstract: Background: Antenatal care is one of the continua of reproductive health care, and inadequate antenatal care utilization results in an adverse feto-maternal outcome. Pregnancy intention is an essential factor that plays a paramount role on timing of antenatal care service. The finding of a few studies conducted on the association between pregnancy intention and late initiation of ANC among pregnant women in Ethiopia presented inconclusive. Therefore, the objective of this systematic review and meta-analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
4
10
0
Order By: Relevance
“…In agreement with existing literature [ 7 , 9 , 11 , 19 , 39 42 , 45 , 57 , 65 ], this study indicated that women with unwanted pregnancy (pregnancy wanted later and no more) were less likely to start the first ANC visit within recommend time compared to women who wanted their pregnancy then. The possible reason might be women having wanted pregnancy has a chance of detecting the pregnancy earlier or women may give more cautious and excited to know their pregnancy status than those who had unwanted pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with existing literature [ 7 , 9 , 11 , 19 , 39 42 , 45 , 57 , 65 ], this study indicated that women with unwanted pregnancy (pregnancy wanted later and no more) were less likely to start the first ANC visit within recommend time compared to women who wanted their pregnancy then. The possible reason might be women having wanted pregnancy has a chance of detecting the pregnancy earlier or women may give more cautious and excited to know their pregnancy status than those who had unwanted pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…According to earlier research, women who initiate ANC later tend to be younger, more gravid or parous, single, of lower socioeconomic status, less educated, and have less access to healthcare services [ 24 , 26 , 34 – 36 ]. Women who experience unplanned pregnancies, find out they are pregnant later than average, and have had healthy pregnancies in the past are also more likely to start ANC later in their pregnancy [ 20 , 30 , 37 39 ]. Additionally, if women have had bad experiences in the past or have a negative perception of the quality of the services, they will not attend ANC [ 30 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the pregnancy period, the findings indicated that women with unplanned pregnancy were more likely to consume cigarettes and alcohol. This was particularly because that unplanned pregnancy was associated with delayed pregnancy recognition, late initiation of antenatal care (Tolossa et al., 2020) and poor knowledge regarding these unhealthy behaviours (Mullan et al., 2016). Thus, health education related to regular antenatal care and adverse outcomes of smoking or alcohol consumption during pregnancy should be promoted especially for those women with unplanned pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy intention is an imperative concept implicated in preconception health (Johnson et al., 2006) and provides opportunity to explore motivation for early intervention. However, few women discussed their pregnancy intentions with healthcare providers (Tolossa et al., 2020). Some women were even not aware of pregnancy when they conceived.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation